auto-update(nvim): 2025-01-31 03:11:45
This commit is contained in:
parent
57767822e3
commit
1e177107d8
1 changed files with 347 additions and 0 deletions
|
@ -276,3 +276,350 @@ The right to left direction is very easy in this case. By directly plugging in $
|
|||
]
|
||||
|
||||
*12a.*
|
||||
|
||||
F. This is a proof that $not A => B$ is a contradiction, which is not
|
||||
sufficient to show $A => B$.
|
||||
|
||||
= 1.6
|
||||
|
||||
*1b.*
|
||||
|
||||
#proof[
|
||||
Consider $m = 1$, $n = -1$. Then $15(1) + 12(-1) = 3$.
|
||||
]
|
||||
|
||||
*1c.*
|
||||
|
||||
Rewrite $2m + 4n = 7$ as $2(m + 2n) = 7$. Notice that $2(m + 2n) = 2k, exists k
|
||||
in nonzero$ and therefore is an even number for any $m$, $n$. But 7 is not
|
||||
even. So no choices of $m$ and $n$ can create a number equal to 7. So no $m$ or
|
||||
$n$ exists.
|
||||
|
||||
*4a.*
|
||||
|
||||
#proof[
|
||||
Consider $x = 2$. Then $x^2 + x + 41 = 46$, which is not prime. So it's false.
|
||||
]
|
||||
|
||||
*4b.*
|
||||
|
||||
#proof[
|
||||
For any $x$, choose $y = -1 dot x$. Then $x + (-x) = x(1 - 1) = 0x = 0$. This
|
||||
is also trivially true when considering our usual field of reals because the
|
||||
existence of $y$ such that $x + y = 0$ is an axiom.
|
||||
]
|
||||
|
||||
*4c.*
|
||||
|
||||
Consider $x = 2$ and $y = 1$. Then $1 > 2$ is false.
|
||||
|
||||
*4d.*
|
||||
|
||||
Consider $a = 10$, $b = 2$, $c = 5$. Then $a | b c$ because $10 | 2 dot 5$ but
|
||||
10 does not divide either 2 or 5.
|
||||
|
||||
*6a.*
|
||||
|
||||
#proof[
|
||||
Rewriting the inequality,
|
||||
$
|
||||
1 / n <= 1\
|
||||
1 <= n
|
||||
$
|
||||
This is true for all $n in NN$ by the definition of $NN$.
|
||||
]
|
||||
|
||||
*6b.*
|
||||
|
||||
#proof[
|
||||
Rewriting,
|
||||
$
|
||||
1 / n < 0.13 \
|
||||
1 < 0.13n \
|
||||
n > 1 / 0.13
|
||||
$
|
||||
So such an $M$ is $1/0.13$, because all naturals greater than $1/0.13$ are
|
||||
greater than $1/0.13$.
|
||||
]
|
||||
|
||||
*6e.*
|
||||
|
||||
#proof[
|
||||
$
|
||||
forall n in NN, n + 1 > n
|
||||
$
|
||||
]
|
||||
|
||||
*6f.*
|
||||
|
||||
$
|
||||
forall k in ZZ, m = -k, k + m = 0 \
|
||||
forall n in NN, 0 <= 0 < n
|
||||
$
|
||||
|
||||
*6i.*
|
||||
|
||||
First consider $K = 10$, and therefore
|
||||
|
||||
$
|
||||
forall r > 10, r^2 > 100
|
||||
$
|
||||
Then note that our inequality is equivalent to $r^2 > 100$, which is true for
|
||||
all $r$.
|
||||
$
|
||||
1 / (r^2) < 0.01 \
|
||||
r^2 > 100 \
|
||||
$
|
||||
So a $K$ exists, namely $K = 10$.
|
||||
|
||||
*6k.*
|
||||
|
||||
Consider $M = 51$. Then $forall r > 51, 2r > 102$ and $2r > 100$ is always
|
||||
true.
|
||||
|
||||
$
|
||||
1 / (2r) < 0.01 \
|
||||
2r > 100
|
||||
$
|
||||
|
||||
So such an $M$ exists, namely, $M = 51$.
|
||||
|
||||
= 2.1
|
||||
|
||||
*4a.*
|
||||
|
||||
False.
|
||||
|
||||
*4b.*
|
||||
|
||||
True.
|
||||
|
||||
*4c.*
|
||||
|
||||
False.
|
||||
|
||||
*4d.*
|
||||
|
||||
True.
|
||||
|
||||
*4e.*
|
||||
|
||||
True.
|
||||
|
||||
*4f.*
|
||||
|
||||
False.
|
||||
|
||||
*4g.*
|
||||
|
||||
True.
|
||||
|
||||
*4h.*
|
||||
|
||||
False.
|
||||
|
||||
*4i.*
|
||||
|
||||
False.
|
||||
|
||||
*4j*.
|
||||
|
||||
True.
|
||||
|
||||
*5a.*
|
||||
|
||||
True.
|
||||
|
||||
*5b.*
|
||||
|
||||
True.
|
||||
|
||||
*5c.*
|
||||
|
||||
True.
|
||||
|
||||
*5d.*
|
||||
|
||||
True.
|
||||
|
||||
*5e.*
|
||||
|
||||
False.
|
||||
|
||||
*5f.*
|
||||
|
||||
True.
|
||||
|
||||
*5g.*
|
||||
|
||||
True.
|
||||
|
||||
*5h.*
|
||||
|
||||
True.
|
||||
|
||||
*5i.*
|
||||
|
||||
False.
|
||||
|
||||
*5j.*
|
||||
|
||||
True.
|
||||
|
||||
*5k.*
|
||||
|
||||
True.
|
||||
|
||||
*5L.*
|
||||
|
||||
True.
|
||||
|
||||
*6a.*
|
||||
|
||||
$
|
||||
A = {1,2}, B = {1,2,3}, C = {1,2,4}
|
||||
$
|
||||
|
||||
*6b.*
|
||||
|
||||
$
|
||||
A = B = C
|
||||
$
|
||||
|
||||
A particular example might be $A = {1}, B = {1}, C = {1}$.
|
||||
|
||||
*6c.*
|
||||
|
||||
$
|
||||
A = {1}, B = {1,2}, C = {3}
|
||||
$
|
||||
|
||||
*6d.*
|
||||
|
||||
$
|
||||
A = {1,2}, B = {1,2,3}, C = {5,6,7}
|
||||
$
|
||||
|
||||
*8.*
|
||||
|
||||
Theorem 2.1.1: $forall A, B, C, A subset.eq B and B subset.eq C => A subset.eq C$.
|
||||
|
||||
#proof[
|
||||
$
|
||||
forall a in A, a in B \
|
||||
forall a in A, exists b in B, a = b \
|
||||
forall b in B, b in C \
|
||||
forall a in A, a in C => A subset.eq C
|
||||
$
|
||||
]
|
||||
|
||||
*11a.*
|
||||
|
||||
#proof[
|
||||
$
|
||||
{x in RR : 3 / 4 x - 2 > 10} \
|
||||
= {x in RR : x > 16 } \
|
||||
= (16, infinity)
|
||||
$
|
||||
]
|
||||
|
||||
*11b.*
|
||||
|
||||
#proof[
|
||||
$
|
||||
{x in RR : |x - 4| = 2|x| - 2} \
|
||||
= {x in RR : |x - 4| = 2|x| - 2} \
|
||||
$
|
||||
|
||||
Now we consider various cases. Consider $x >= 4$. Then
|
||||
$
|
||||
{x in RR : x - 4 = 2x - 2} \
|
||||
= {x in RR : x - 4 = 2x - 2} \
|
||||
= {x in RR : x = -2} \
|
||||
$
|
||||
But in this case $x >= 4$. Since there is no $x >= 4$ such that $x = -2$,
|
||||
this is actually $emptyset$.
|
||||
|
||||
Now consider $0 <= x < 4$.
|
||||
$
|
||||
{x in RR : 4 - x = 2x - 2} \
|
||||
= {x in RR : x = 2} \
|
||||
= {2}
|
||||
$
|
||||
|
||||
|
||||
Now consider $x < 0$. Then
|
||||
$
|
||||
{x in RR : 4 - x = -2x - 2} \
|
||||
{x in RR : x = -6}
|
||||
$
|
||||
So the set contains $6$ when $x < 0$.
|
||||
|
||||
And since these inequalities span all $x in RR$, the only members of
|
||||
the set are ${2, -6}$.
|
||||
]
|
||||
|
||||
*11c.*
|
||||
|
||||
#proof[
|
||||
$
|
||||
{x in RR : 2|x+3| + x = 0}
|
||||
$
|
||||
For $x >= -3$, we have
|
||||
$
|
||||
{x in RR : 2(x + 3) + x = 0} \
|
||||
= {x in RR : x = -2} \
|
||||
= {-2}
|
||||
$
|
||||
For $x < -3$, we have
|
||||
$
|
||||
{x in RR : 2(3 - x) + x = 0} \
|
||||
= {x in RR : x = 6 } \
|
||||
= {6}
|
||||
$
|
||||
And since these inequalities partition $RR$ the original set is ${-2, 6}$.
|
||||
]
|
||||
|
||||
*11d.*
|
||||
|
||||
$
|
||||
{x in RR : |x| = 6 - |2x|}
|
||||
$
|
||||
|
||||
Consider $x >= 0$. Then
|
||||
$
|
||||
{x in RR : x = 6 - 2x} \
|
||||
= {x in RR : x = 2}
|
||||
$
|
||||
Consider $x < 0$. Then
|
||||
$
|
||||
{x in RR : -x = 6 + 2x} \
|
||||
= {x in RR : x = -2}
|
||||
$
|
||||
So
|
||||
$
|
||||
{x in RR : |x| = 6 - |2x|} = {-2, 2}
|
||||
$
|
||||
|
||||
*11e.*
|
||||
|
||||
$
|
||||
{x in RR : |x + 3| <= -4x - 2}
|
||||
$
|
||||
|
||||
Consider $x >= -3$. Then
|
||||
$
|
||||
{x in RR : x <= -1} \
|
||||
= (-infinity, -1]
|
||||
$
|
||||
|
||||
Now consider $x < -3$ Then
|
||||
$
|
||||
{x in RR : 3 - x <= -4x - 2} \
|
||||
= {x in RR : x <= -5 / 3} \
|
||||
= (-infinity, -5 / 3]
|
||||
$
|
||||
But $(-infinity, -5/3) union (-infinity, 1] = (-infinity, 1]$ so that is our
|
||||
answer.
|
||||
|
||||
*11f.*
|
||||
|
|
Loading…
Reference in a new issue